2023
DOI: 10.3390/ijms242216095
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Psoriasis: A Comprehensive Review

Alessandra-Mădălina Man,
Meda Sandra Orăsan,
Oana-Alina Hoteiuc
et al.

Abstract: Psoriasis is an immune-mediated disease with a strong genetic component that brings many challenges to sick individuals, such as chronic illness, and which has multiple associated comorbidities like cardiovascular disease, metabolic syndrome, inflammatory bowel disease, and psychological disorders. Understanding the interplay between the innate and adaptative immune system has led to the discovery of specific cytokine circuits (Tumor Necrosis Factor-alpha (TNF-α), IL-23, IL-17), which has allowed scientists to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 212 publications
(207 reference statements)
0
5
0
1
Order By: Relevance
“…Established studies have shown that chronic inflammation of the skin is not only a local problem. It induces inflammation in organs throughout the body, causing cardiovascular and cerebrovascular disorders, systemic amyloidosis, and other organ damage [ 20 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Furthermore, it is known to induce inflammation in adipose tissue, with known effects such as weight loss due to adipose tissue atrophy, decreased heat production capacity, and increased production of inflammatory adipocytokines [ 23 , 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Established studies have shown that chronic inflammation of the skin is not only a local problem. It induces inflammation in organs throughout the body, causing cardiovascular and cerebrovascular disorders, systemic amyloidosis, and other organ damage [ 20 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Furthermore, it is known to induce inflammation in adipose tissue, with known effects such as weight loss due to adipose tissue atrophy, decreased heat production capacity, and increased production of inflammatory adipocytokines [ 23 , 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between psoriasis and obesity has been a subject of increasing interest within the medical research community [4][5][6] , given the growing evidence suggesting that obesity, as a prevalent and potentially modi able risk factor, can exacerbate the clinical trajectory of psoriasis and vice versa 4,6,7 . It was found that the in ammatory pathways shared between obesity and psoriasis, which involve cytokines such as TNF-α and IL-6, may suggest a biological plausibility for their bidirectional correlations [8][9][10] . Both conditions are associated with a heightened risk of mortality 3,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Affected skin may be degenerated to silver, white, or red with scaly plaques [2]. Itching, scaling, burning, erythema, and bleeding are the most routine psoriasis symptoms [3]. About 3 % of the world's population (around 125 million persons) is affected by psoriasis, with up to 30 % frequency of complicated cases [4].…”
Section: Introductionmentioning
confidence: 99%